HUMAN DEVELOPMENT INDICATORS OF AREAS ASSESSED BY A FOREST FOMENTATION PROGRAM - Rezende, José Luiz Pereira de (2015)
The Index of Human Development – IDH – was proposed by PNUD for measuring the development of population life quality. The IDH takes into consideration the income, the education level and the longevity. The monitoring of this index, over time, can constitute in an analysis tool for measuring the influences of the public policy on human development in a region. In the Minas Gerais State the forest activity has been promoted by the fomentation program called Asiflor-IEF in various regions as way to indicate social and and economic development. This work built a report base using the characterization of the current indexes of IDH of counties assisted by each regional office of IEF to serve as future comparisons to indicate the contribution of the forest fomentation in the improvement of IDH. The Atlas of Human Development of Brazil was used to define the areas of interest, i.e., the involved regional offices and to establish the on going IDH indexes. For all offices, the component of the IDH that determined the lowest value was income. The Regional of the Alto Paranaíba presented the most homogeneous IDH distribution for all counties and the counties belonging to Rio Doce Regional office presented the lowest IDH indexes. It is expected that the forest fomentation program will affect positively and more directly the income variable in future IDH evaluations.